Characterization of cryopreserved primary human corneal endothelial cells cultured in human serum-supplemented media - Vianna,Lucas Monferrari Monteiro (2016)
ABSTRACT Purpose: To compare cryopreserved human corneal endothelial cells (HCECs) grown in human serum-supplemented media (HS-SM) with cryopreserved HCECs grown in fetal bovine serum-supplemented media (FBS-SM). Methods: Three pairs of human corneas from donors aged 8, 28, and 31 years were obtained from the eye bank. From each pair, one cornea was used to start a HCEC culture using HS-SM; the other cornea was grown in FBS-SM. On reaching confluence, the six cell populations were frozen using 10% dimethyl sulfoxidecontaining medium. Thawed cells grown in HS-SM were compared with those grown in FBS-SM with respect to morphology, growth curves, immunohistochemistry, real time-reverse transcriptase polymerase chain reaction (RT-PCR) for endothelial cell markers, and detachment time. Results: No difference in morphology was observed for cells grown in the two media before or after cryopreservation. By growth curves, cell counts after thawing were similar in both media, with a slight trend toward higher cell counts in FBS-SM. Cells grown in both the media demonstrated a similar expression of endothelial cell markers when assessed by immunohistochemistry, although HCEC marker gene expression was higher in cells grown in HS-SM than in those grown in FBS-SM as assessed by RT-PCR. With FBS-SM, there was a tendency of longer detachment time and lower cell passages. Conclusions: HS-SM was similar to FBS-SM for cryopreservation of cultured HCECs as assessed by analysis of cell morphology, proliferation, and protein expression, although marker gene expression was higher in cells grown in HS-SM than in those grown in FBS-SM. Detachment time was longer with FBS-SM and in lower passages.